Engineering surface states and band edge of TiO2 microspheres by tuning pH value of hydrothermal treatment. (1st September 2018) - Gao, Chun; Ding, You-Cai; Mo, Li-E; Li, Zhao-Qian; Shi, Xiao-Qiang; Hu, Lin-Hua; Hayat, Tasawar; Alsaedi, Ahmed; Dai, Song-Yuan
Abstract: Herein, TiO2 microspheres were synthesized at different pH values. The effects of pH values on surface states and charge transport performances were investigated. It is noted that alkaline environment leads to a negative band edge of TiO2 microsphere and promotes the interfacial charge transfer. Meanwhile, the charge recombination in the TiO2 microspheres was effectively suppressed in alkaline environment. Besides, TiO2 microspheres synthesized in alkaline condition contained less surface states, which is beneficial to a higher charge collection efficiency and longer diffusion length in dye sensitized solar cells (DSSCs). Moreover, a better crystallinity of TiO2 microspheres can be obtained in an alkaline environment. As a result, when these TiO2 microspheres were used in DSSCs, the device with the TiO2 synthesized at pH = 8 showed the highest performance than that of the device based on TiO2 synthesized in lower pH values. Graphical abstract: The density of surface states and band edge shifts of four TiO2 submicrospheres with different crystallinity were investigated. The discussion not only provide a new vision on the surface states of TiO2 microspheres, but also exploit the influence of band edge shifts to electron transfer and recombination. Image 1